RESISTING SOVEREIGN SURVEILLANCE: AN ACTIVIST AGENDA FROM THE INCARCERATED - Lingel, Jessa; Sinnreich, Adam (AoIR Selected Papers of Internet Research, 2014)
In the wake of recent disclosures about government surveillance, longstanding questions of privacy and individual control of information have become vitally and politically important. Although there is much that we do not know about the extent of who is watching and what happens to the data generated by these actions, we do know that surveillance is constant and wide reaching, such that it can be difficult to imagine technological practices that would ensure privacy, whether of cell phone use, search engine queries or emailing. In order to suggest an activist agenda for protesting infrastructures of surveillance, this paper draws on practices of resistance among populations that have extensive experience with near-totalizing mechanisms of monitoring and control - the incarcerated. Institutional monitoring of prisoners typically encompasses clothing, food, visitors, medication and communication, where part of the loss of subjectivity and selfhood that prisoners frequently report is tied to the inability to experience any sense of personal privacy (Passmore, 2009; Ziarek, 2008).